Engaging Learners in Critical Analysis Through Concept Maps: From Theory to Practice - Susan M. Yelich-Biniecki (Adult Education Research Conference, 2014)
This paper addresses the use of concept maps to engage adult learners in critical analysis. The discussion is situated within four adult learning theories. Examples from different contexts using concept maps and connections between theories, learning process, locus of learning, teacher’s role, manifestation in adult education, and activities are presented.